Role of the endothelial cell apolipoprotein E receptor 2 in modulating the effects of apoE3 and apoE4 on insulin blood-brain barrier transport - Peter Thomas; Van Nguyen; Riley Weaver; Kim Hansen; Anastasia Sacharidou; William A. Banks; Chieko Mineo; Philip W. Shaul; Elizabeth M. Rhea (PLoS ONE, 2026)
Apolipoprotein E receptor 2 (apoER2), a primary receptor for apoE, has recently been linked to Alzheimer’s disease. Compared with the most common form of apoE, apoE3, the apoE4 isoform increases the risk for developing Alzheimer’s disease. ApoE4 impairs brain insulin signaling, a feature of Alzheimer’s disease that correlates with cognitive decline. Insulin availability in the brain largely depends on blood-brain barrier (BBB) transport and contributes to brain insulin signaling. We have previously shown that the apoE4 isoform leads to regional reductions in insulin BBB transport in mice on a Western diet compared to apoE3 isoform. However, how insulin transport across the BBB is regulated by apoE isoforms is not well understood. Here we investigated a role of endothelial apoER2 in the effects of apoE isoforms on insulin BBB transport, using mice genetically expressing human apoE3 or apoE4 and expressing or lacking endothelial apoER2. We found that a loss of endothelial apoER2 did not overtly affect insulin BBB transport in either apoE3- or apoE4-expressing mice, except in the frontal cortex and pons/medulla, where decreased transport was observed in apoE3 mice lacking endothelial apoER2. These findings indicate that the effect of apoE4 on insulin BBB transport is largely independent of endothelial apoER2. In contrast, endothelial apoER2 may regulate insulin BBB transport in limited regions of the brain through its binding to apoE3.